Relationship Between Business Models of Banks and Stability of Economic Development - G. G. Gospodarchuk; A. V. Aistov; E. O. Suchkova (Финансы: теория и практика)
Depending on the chosen business model, banks can act as both shock absorbers and crisis catalysts. In this regard, the analysis of the relationship between banks’ business models and financial cycles becomes a useful tool for diagnosing and predicting crisis phenomena. The purpose of the research is to identify the relationship between the volume of debt of the banking and the debt burden of the economy. The research uses econometric methods. The key result of the research is two new econometric models, which were calibrated for the Russian economy. The models differ from each other by the types of bank liabilities used in the calculation of independent variables. The models also differ from the existing models by the calculation algorithm of independent variables. The source of information is the official statistics of the Bank of Russia for the period 2008–2019. The tests of the models confirmed the presence of a statistically significant cointegration relationship between the debt burden of the banking sector and the debt burden of the economy. Coupling coefficients in the models are identified as debt multipliers of the banking sector and characterize the multiplier effect of changes in the debt burden of banks. For the model containing banks’ balance sheet liabilities, the debt multiplier for the Russian economy was 6.7; and for the model using banks’ total liabilities was 3.1. The developed models are easy-to-use for forecasting financial cycles.